Responses and preferences of rural Islamic university EFL learners for written corrective feedback (Englisia : Journal of Language, Education, and Humanities, 2023)
The primary objective of this current investigation was to provide a detailed account of the experiences of English as Foreign Language (EFL) learners in their response to Written Corrective Feedback (WCF). Additionally, the study aimed to explore the preferences of these learners regarding the utilization of WCF in their thesis writing within the context of a rural Islamic higher education institution. The participants of this study consisted of twenty-two senior EFL learners who were in the process of writing their theses as their final projects. To gather the necessary data, semi-structured interviews were extensively utilized. The findings of this study revealed that EFL learners employed various strategies when responding to WCF, including a focus on grammatical error correction, an emphasis on overall error correction, the utilization of online grammar checkers, and seeking guidance from their supervisors. Furthermore, the learners' perception of WCF included their preferences, disfavored aspects, advantages, and disadvantages. These results indicate that EFL learners are expected to engage in intensive learning of grammar and writing. Additionally, it is crucial to establish standardized approaches to providing WCF. In conclusion, WCF proves to be a valuable tool for EFL learners in their thesis writing endeavors.
Keywords: written corrective feedback; EFL learners; thesis writing